Synthesis and Characterization of Carbazole Based Donor-Acceptor-Donor Type Polymer for NLO Applications. (March 2020) - Balakrishna, K.; Sampath, R.; Vishwam, T.; Samui, A. B. M.; Joshi, P.; Mohan, S.Raj
Abstract: Carbazole based NLO polymer was synthesized by using Knoevenagel condensation. The polymer is found to be fully soluble in high polar solvents like dimethyl formamide and dimethylsulphoxide. By using GPC and tetrahydrofuran as a solvent, the molecular weight is found to be 5000 g/mol. Thermal analysis exhibited thermal stability of the polymer up to 400 °C and glass transition temperature (Tg) at 214 °C. The polymer film has good optical transparency. The non-centrosymmetry in the film was induced by corona poling for second order NLO property, whereas z-scan technique is used to understand third order NLO property. The effective TPA coefficient (β) found to be 5.1 X 10 −12 m/W. Computational study indicated that the total charge is located at the center of the molecule in HUMO case whereas in the case of LUMO the charge is spreads out from the center of the molecule.